New lives for old : cultural transformation - Manus, 1928-1953 - Mead, Margaret 1901-1978 (Perennial Edition, 2001)
When Margaret Mead first studied the Manus Islanders of New Guinea in 1928, they were living with a Stone Age technology. Economically vulnerable and burdened by a complex moral code, the Manus seemed ill-equipped to handle the massive impact that World War II had on their secluded world. But a unique set of circumstances allowed the Manus to adapt swiftly to the twentieth century, and their experience led Mead to develop a revolutionary theory of cultural transformation, one that favors rapid, over piecemeal, change. As relevanttoday as it was a half-century ago, New Lives for Old is an optimistic examination of one society that chose to change, offering hope and a valuablemodel for today's developing societies. This edition, prepared for the centennial of Mead's birth, features introductions by Stewart Brand and Mead's daughter, Mary Catherine Bateson.